2014
DOI: 10.1186/1742-2094-11-114
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 beta guides the migration of cortical neurons

Abstract: BackgroundProinflammatory cytokine interleukin-1beta (IL-1β) is expressed at high levels in the developing brain and declines to low constitutive levels in the adult. However, the pathophysiological function of IL-1β during brain development remains elusive. In this study, we investigated the role of IL-1β in neuronal migration.MethodsThe Boyden transwell assay was used to examine the effects of IL-1β on the migration of dissociated primary cortical neurons. To determine the role of IL-1β in neuron leading pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 37 publications
2
27
0
1
Order By: Relevance
“…On the contrary, IL-1β showed beneficial effects on neuronal survival in cultures; it is highly expressed in the developing brain and can directly influence neural precursor cells (NPCs) [ 6 ]. In other in vitro models, IL-1β has been shown to stimulate the migration of cultured cortical neurons and promote neurite outgrowth [ 1 , 7 ]. The findings in various neuronal culture models show that long-term exposure (3–5 days) to high concentrations of IL-1β (500 ng/ml) had neurotoxic effects; however, short-term exposure (1 day) to lower concentrations (10 ng/ml) did not [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, IL-1β showed beneficial effects on neuronal survival in cultures; it is highly expressed in the developing brain and can directly influence neural precursor cells (NPCs) [ 6 ]. In other in vitro models, IL-1β has been shown to stimulate the migration of cultured cortical neurons and promote neurite outgrowth [ 1 , 7 ]. The findings in various neuronal culture models show that long-term exposure (3–5 days) to high concentrations of IL-1β (500 ng/ml) had neurotoxic effects; however, short-term exposure (1 day) to lower concentrations (10 ng/ml) did not [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that IL-1ß can stimulate migration of neurons and guide axonal growth cone turning, essential for forming tangential connections between neuronal columns. [ 155 ] TNF-α has also been shown to play a critical role in brain development, but as with other cytokines, depends on careful control of its concentration [ Figure 3 ]. For example, high levels of TNF-α have been shown to inhibit neurite outgrowth and branching in embryonic hippocampal neurons.…”
Section: Cytokines and Chemokines In Autism Spectrum Disorder And Neumentioning
confidence: 99%
“…• ИЛ 1β регулирует миграцию клеток астроглиальной и нейрональной природы в процессе нейрогенеза [14].…”
Section: цитокинпродуцирующая активность клеток при нейровоспалении иunclassified